SMEDIS: scientific model evaluation of dense gas dispersion models. (1st January 2000) - Daish, N.C.; Britter, R.E.; Linden, P.F.; Jagger, S.F.; Carissimo, B.
SMEDIS is a project currently in progress to develop a protocol for the scientific evaluation of dense gas dispersion (DGD) models, with particular emphasis on the complex effects of obstacles, terrain and aerosols often found in real situations, and then to apply this protocol to DGD models currently in use in Europe. This paper describes the general features of a model evaluation project and then outlines the implementation in the specific case of SMEDIS. The paper concludes with some experiences from the project to date.